Enhancing the contractual provision for suspension of work in Malaysia: a comparative analysis with emphasis on a case study of government contract form PWD203A - Ahmad Anwar, Anisha Syazwani; Mohd-Danuri, Mohd Suhaimi; Mahdzir, Mazura; Mustafa, Muhammad Hadi; Syed Khuzzan Alhabshi, Sh Mazlina (Malaysian Institute Of Planners, 2024)
The government possesses the authority to halt or delay work on-site, either partially or entirely, through the suspension of works as outlined in Clause 50 of the Public Works Department's PWD203A contract form. However, the global outbreak of covid-19 pandemic has revealed the lack of attention towards the proper implementation of work suspension. this study proposes for the improvement of contractual procedures and provisions on the suspension of works of government projects. It addresses the issues pertaining to work suspension, examines the existing contract provision in the contract forms and suggest enhancements of government project contracts. Through a comparative analysis and case study approach focusing on PWD203A, this study identifies the need for establishing clear suspension of work activities, and a fair time restriction mechanism as crucial enhancement to be incorporated into contractual provisions of work suspension. Subsequently, an expert validation process validates the proposed enhancement of the contractual provisions. These findings offer stakeholders valuable insights into practical solutions for more effective management of work suspension of government projects.